1995
DOI: 10.1111/j.1365-2133.1995.tb02678.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive squamous cell carcinomas developing in patients receiving long-term azathioprine

Abstract: We report three patients who developed unusually aggressive squamous cell carcinomas after receiving long-term azathioprine treatment for dermatological disorders. Two patients gave a history suggestive of moderate to excessive sun exposure, and the third suffered from chronic actinic dermatitis. Hence, ultraviolet light damage may have been a significant cofactor in the development of these malignancies. Careful follow-up is necessary in patients who are taking azathioprine long term, and who have previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…Other early clinical data confirmed an increased lymphoma incidence with AZA, even after short-term use (59). In addition to the increased risk for lymphomas, AZA has also been correlated with induction of a broad variety of solid neoplasms, including squamous cell carcinoma (60,61), urinary bladder tumors (62), breast cancer (63), and brain tumors (64). However, with the more recent use of new combined immunosuppressive regimens, the effects of less intensive use of AZA on tumor development in a transplant situation become difficult to assess.…”
Section: Azathioprinementioning
confidence: 98%
“…Other early clinical data confirmed an increased lymphoma incidence with AZA, even after short-term use (59). In addition to the increased risk for lymphomas, AZA has also been correlated with induction of a broad variety of solid neoplasms, including squamous cell carcinoma (60,61), urinary bladder tumors (62), breast cancer (63), and brain tumors (64). However, with the more recent use of new combined immunosuppressive regimens, the effects of less intensive use of AZA on tumor development in a transplant situation become difficult to assess.…”
Section: Azathioprinementioning
confidence: 98%
“…279,280 Aggressive squamous cell carcinoma has been reported in dermatology patients with type 1 skin and greater than 4 years of azathioprine therapy. 281 Those with more immune suppression, such as heart transplantation patients, appear to be at greater risk than those with lesser suppression, like kidney transplantation patients. 279,282 One study showed a lag phase of 3½ years between the initiation of immunosuppressive therapy and the appearance of premalignant lesions.…”
Section: Uncommon Side Effectsmentioning
confidence: 98%
“…[10][11][12] Extended therapy with azathioprine has been found to confer an increased incidence of nonmelanoma skin cancer. 13,14 A large metaanalysis of patients with inflammatory bowel disease treated with thiopurines identified a pooled adjusted hazard ratio for nonmelanoma skin cancer of 2.28. 15 For populations where the base rates of nonmelanoma skin cancer are substantial, a 2-fold increase can be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%